Nature of Hydrocarbon Fluids at the Fields in the North of Western Siberia: the Geochemical Aspect; Geochemistry International; Vol. 61, iss. 2 - Goncharov I. V. Ivan Vasilyevich; Veklich M. A. Maksim Aleksandrovich; Oblasov N. V. Nikolay Vladimirovich; Samoylenko V. V. Vadim Valerjevich; Fadeeva S. V. Svetlana Vasilievna; Kashapov R. S. Roman Sergeevich; Trushkov P. V. Pavel Valerjevich; Zherdeva A. V. Aleksandra Valerievna; Smirnova N. A. Nataljya Aleksandrovna (2023, 2023)
Title screen